2021
DOI: 10.1002/adhm.202100706
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Imaging and Photodynamic Inactivation of Bacteria Based on Cationic Cyclometalated Iridium(III) Complexes with Aggregation‐Induced Emission Properties

Abstract: Antibacterial photodynamic therapy (PDT) is one of the emerging methods for curbing multidrug‐resistant bacterial infections. Effective fluorescent photosensitizers with dual functions of bacteria imaging and PDT applications are highly desirable. In this study, three cationic and heteroleptic cyclometalated Ir(III) complexes with the formula of [Ir(CˆN)2(NˆN)][PF6] are prepared and characterized. These Ir(III) complexes named Ir(ppy)2bP, Ir(1‐pq)2bP, and Ir(2‐pq)2bP are comprised of three CˆN ligands (i.e., 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…Ir(III) complexes have aroused great research interest in phototherapy owing to their favorable characteristics, such as their high ISC ability and tunable photophysical properties. [199][200][201][202][203][204][205][206] In 2017, Chao et al reported a series of Ir(III) complexes with AIE characteristics for cancer cellspecific mitochondria-targeted PDT. The obtained AIE-active Ir(III) complexes exhibited gradually red-shifted emission peaks and gradually decreased quantum yields in the aggregate state from Ir1 to Ir3.…”
Section: Organometallic Aiegensmentioning
confidence: 99%
“…Ir(III) complexes have aroused great research interest in phototherapy owing to their favorable characteristics, such as their high ISC ability and tunable photophysical properties. [199][200][201][202][203][204][205][206] In 2017, Chao et al reported a series of Ir(III) complexes with AIE characteristics for cancer cellspecific mitochondria-targeted PDT. The obtained AIE-active Ir(III) complexes exhibited gradually red-shifted emission peaks and gradually decreased quantum yields in the aggregate state from Ir1 to Ir3.…”
Section: Organometallic Aiegensmentioning
confidence: 99%
“…For instance, rose bengal and chlorin e6 (20 μM) inactivated only 0.6 and 1.2 log 10 of S. aureus with high light doses of 30 and 20 J/cm 2 , respectively. It is worth noting that the light dose needed to effectively kill S. aureus (>3.0 log 10 ) with CPVBP2 (1.2 J/cm 2 ) is also significantly lower than many reported photosensitizers, including traditional photosensitizers, such as porphyrin, phthalocyanine, phenothiazinium, boron-dipyrromethene, indocyanine green, and AIE photosensitizers. , …”
Section: Resultsmentioning
confidence: 93%
“…Instruments. 1 H and 13 C NMR spectra were measured using a Bruker BioSpin AVANCE III 400 MHz spectrometer and a JEOL EZC400S 400 MHz spectrometer. High-resolution mass spectra (HRMS) were obtained on a Bruker Impact II Mass Spectrometer.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38] To achieve an efficient PDT process, photosensitizers (PSs) [39][40][41][42] with excellent reactive oxygen species (ROS) generation ability are highly desired. 43,44 In biologically relevant processes, however, the chemical structures, the physiological environments, [45][46][47] and the self-assembled forms [48][49][50] of PSs have a salient influence on the inherent properties including the ROS generation ability as well as the emission behaviors. 51,52 For example, the photophysical behaviors in both isolated and aggregate states are easily tuned by molecular engineering such as simple alteration of substituent positions and species.…”
Section: Introductionmentioning
confidence: 99%